Nonlocal Integrodifferential Boundary Value Problem for Nonlinear Fractional Differential Equations on an Unbounded Domain - Lihong Zhang; Bashir Ahmad; Guotao Wang; Ravi P. Agarwal; Maryem Al-Yami; Wafa Shammakh (Abstract and Applied Analysis)
This paper investigates the existence of nonnegative solutions for nonlinear fractional differential equations with nonlocal fractional integrodifferential boundary conditions on an unbounded domain by means of Leray-Schauder nonlinear alternative theorem. An example is discussed for the illustration of the main work.